Perception of violence in university students in relation to gender and place - Navarro-Castillo, Yulissa (2022)
Latin America is one of the most violent regions in the world, and unfortunately Peru is included among the most violent countries in the region. This affects not only the victims but also society and this also translates into economic losses and limitations to achieve the well-being of its citizens. For example, in Peru, at least 63.2% of women have been victims of some type of violence in 2018 (INEI, 2019), and the place of occurrence is not only homes, but also other spaces. social institutions that are perceived as safe such as educational institutions, or universities. Based on the above, an exploratory research is presented that shows the perception of university students regarding the level and type of violence they have suffered. To provide a better view of the problem, variables that complement the study were analyzed, such as gender, type of violence and the most recurrent places where these unfavorable scenarios for a person’s development occur. In the results presented, it was found that at least 56% of those surveyed have perceived being victims of violence.